Wrong Hand, Wrong Children? The Education of Left-Handed Children in Soviet Latvia - Rubene, Zanda; Daniela, Linda; Medne, Dace (Acta Paedagogica Vilnensia, 2019)
Left-handers have always been surrounded by stigma and controversy, and attitudes toward this group have always been rooted in the ideas and traditions of power relations existing in a given society. Thus, the goal of this study is to describe the retraining of left-handers as it was conducted in Soviet education. The impact of political power on an individual’s body-mind interaction is a significant problem in research on the creation of the “New Soviet Man.” The teaching of left-handed children in the Soviet Union is a noteworthy example of the totalitarian regime’s illusionary endeavors to change human nature. The Soviet education envisaged neither a special attitude nor any particular pedagogical strategies for the work with left-handed children. The Soviet science was based on the anthropological understanding of man as a tabula rasa, which made it possible to explain the omnipotence of Soviet pedagogy as well as the unswerving belief that it was possible to educate every child into a true member of the socialist society. The present study provides insight into the disciplining of the left-handed children’s bodies and minds using pedagogical tools that was being conducted in Soviet Latvia.
Keywords: education of left-handed children; disciplining of the body and mind; Soviet education; project of the “New Soviet man”